1989
DOI: 10.1103/physreva.40.1315
|View full text |Cite
|
Sign up to set email alerts
|

Angular distribution of electrons elastically scattered from hydrogen atoms

Abstract: Absolute elastic differential cross sections of atomic hydrogen have been measured by a modulated crossed-beam method. The energy and angular range covered were from 5 to 30 eV and from 12' to 156', respectively. The present results agree with the previous measurements within the experimental uncertainty below 15 eV, but it is found that the present results show stronger backward scattering () 120') than the previous measurement and theoretical results by more than a factor of 2 above 20 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Laboratory measurements of the e-H momentum transfer cross sections have been performed by Williams (1975a,b); Callaway & Williams (1975); Shyn & Cho (1989); Shyn & Grafe (1992) (for a detailed review of the experimental methods and results, see Bederson & Kieffer 1971;Trajmar & Kanik 1995). Theoretical and experimental results are shown in Fig.…”
Section: E -Hmentioning
confidence: 99%
“…Laboratory measurements of the e-H momentum transfer cross sections have been performed by Williams (1975a,b); Callaway & Williams (1975); Shyn & Cho (1989); Shyn & Grafe (1992) (for a detailed review of the experimental methods and results, see Bederson & Kieffer 1971;Trajmar & Kanik 1995). Theoretical and experimental results are shown in Fig.…”
Section: E -Hmentioning
confidence: 99%
“…( 14) of Draine (1983) for the same values of the drift velocity (dotted curve).The dashed line shows the Langevin rate. fer cross sections have been performed by Williams (1975a,b), Callaway & Williams (1975), Shyn & Cho (1989), and Shyn & Grafe (1992) (for a detailed review of the experimental methods and results, see Bederson &Kieffer 1971 andKanik 1995). Theoretical and experimental results are shown in Fig.…”
Section: E -Hmentioning
confidence: 99%
“…In the case of electrons, the collisions can be elastic or inelastic depending on the energies of the particles involved. Collision cross sections have been taken from the literature [2,11,[16][17][18][19] (figure 2). They consist of only the most important reaction paths.…”
Section: The Instant Of Collisionmentioning
confidence: 99%
“…In this investigation the hard sphere model is preferred, because in the case of hydrogen equation (4) strongly overestimates the variation in the differential cross section with electron energy. For example, the differential cross sections of hydrogen atoms have been found to be nearly independent of the scattering angle at an electron energy of 5 eV [17], while equation (4) suggests a sixfold higher cross section at χ = 0 • compared to χ = 180 • . Nevertheless, we tried equation ( 5) in our code but found that the sum of the power shares of the different processes is then approximately 25-30% higher than the input power.…”
Section: Elastic Collisionsmentioning
confidence: 99%